Ir(III) Metal Emitters with Cyano‐Modified Imidazo[4,5‐b]pyridin‐2‐ylidene Chelates for Deep‐Blue Organic Light‐Emitting Diodes - Wu, Yixin; Xin, Yangyang; Pan, Yi; Yiu, Shek‐Man; Yan, Jie; Lau, Kai Chung; Duan, Lian; Chi, Yun (Advanced science, 2024)
Ir(III) carbene complexes have been explored as one of the best blue phosphors for their high performance. Herein, the authors designed and synthesized a series of blue‐emitting Ir(III) phosphors (f‐ct9a–c), featuring fac‐coordinated cyano‐imidazo[4,5‐b]pyridin‐2‐ylidene cyclometalates. These Ir(III) complexes exhibit true‐blue emission with a peak maximum spanning 448–467 nm, with high photoluminescence quantum yields of 81–88% recorded in degassed toluene. Moreover, OLED devices bearing phosphors f‐ct9a and f‐ct9b deliver maximum external quantum efficiencies (EQEmax) of 25.9% and 30.3%, together with Commission Internationale de L'Eclairage (CIEx,y) coordinates of (0.157, 0.225) and (0.142, 0.169), respectively. Remarkably, the f‐ct9b‐based device displays an incredible EQE of 29.0% at 5000 cd·m−2. The hyper‐OLED device based on f‐ct9b and ν‐DABNA exhibits an EQEmax of 34.7% and CIEx,y coordinates of (0.122, 0.131), affirming high potentials in achieving efficient blue electroluminescence. A new class of blue emissive Ir(III) complexes bearing facially arranged cyano‐modified imidazo[4,5‐b]pyridin‐2‐ylidene chelates are reported, showing high emission quantum yields and short radiative lifetimes. In addition to the efficient blue electrophosphorescence, one hyper‐OLED device delivers a narrowband blue emission with CIEy coordinate of 0.123, EQEmax of 32.1%, and EQE of 21.3% at 5000 cd·m−2, respectively.